2007
DOI: 10.1016/j.febslet.2006.12.043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pleiotrophin signaling on adipogenesis

Abstract: Pleiotrophin (PTN) plays diverse roles in cell growth and differentiation. In this investigation, we demonstrate that PTN plays a negative role in adipogensis and that glycogen synthase kinase 3b (GSK-3b) and b-catenin are involved in the regulation of PTN-mediated preadipocyte differentiation. Knocking down the expression of PTN using siRNA resulted in an increase in phospho-GSK-3b expression, and the accumulation of nuclear b-catenin, which are critical downstream signaling proteins for both the PTN and Wnt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 40 publications
1
48
1
1
Order By: Relevance
“…As a growth factor, PTN stimulates the mitogenesis of fibroblasts, endothelial cells, and epithelial cells in culture, as well as neurite outgrowth in neonatal neuronal cells [51, 52]. Homeostasis of endometrial tissue plays an important role in the preparation of the uterus for each new estrous cycle or to support pregnancy [41].…”
Section: Resultsmentioning
confidence: 99%
“…As a growth factor, PTN stimulates the mitogenesis of fibroblasts, endothelial cells, and epithelial cells in culture, as well as neurite outgrowth in neonatal neuronal cells [51, 52]. Homeostasis of endometrial tissue plays an important role in the preparation of the uterus for each new estrous cycle or to support pregnancy [41].…”
Section: Resultsmentioning
confidence: 99%
“…For example, it was shown to promote the apoptotic response of cardiomyocytes through the inhibition of Akt signaling (55) and to inhibit angiogenesis by interfering with VEGF165 (56). Moreover, it has been shown that pleiotrophin negatively regulates adipogenesis (35). In addition, several publications have reported contradictory results concerning the activities of pleiotrophin.…”
Section: Discussionmentioning
confidence: 99%
“…10 Thus, Ptn increases the phosphorylation status of various substrates of Ptprz1, including Ctnnb1. 10,23,24 We and others have previously shown that Ctnnb1 is an important regulator of HSC self-renewal and differentiation. 4,25,26 However, coculture with Ptn-knockdown stromal cells did not affect Ctnnb1 expression, neither at the mRNA or at the protein level nor in the distribution between cytoplasm and nucleus in sorted LSK, CMP, or GMP from stromal cocultures.…”
Section: Discussionmentioning
confidence: 99%